Introducing Technology for Bedside Nurses: A New Department for Critical Care Practice. - Alderden, Jenny G.; Goforth, Carl (Critical Care Nurse, 2026)
The article focuses on the integration of advanced technology in critical care units by 2026, highlighting both benefits and challenges for bedside nurses. Technologies such as intravenous smart pumps, artificial intelligence (AI) algorithms, smart beds, and tele–intensive care units (tele-ICUs) have improved patient monitoring, safety, and workflow efficiency, while also raising concerns about alert fatigue, workflow fragmentation, and maintaining human interaction in care. The new recurring department, Technology for Bedside Nurses, aims to provide practical guidance for nurses to thoughtfully evaluate, implement, and manage these technologies without compromising clinical judgment or patient relationships. Emphasizing that technology should support rather than replace nursing practice, the department will address issues like alert fatigue, AI decision support, and workflow optimization to help nurses balance technological advances with compassionate care.